Mesma informação, novas aplicações: revisitando primers do gene COI em aves e melhorando a identificação por DNA barcoding - Melo, Amanda Alves de (2021)
Molecular identification of species occurs through the comparison of either morphological, biochemical or genetic characteristics. All of these areas of knowledge for delimiting species are connected and should be analyzed as a complement to fill gaps of information of each area. The process of molecular identification of species through comparison of genetic information named DNA barcode consists of analyzing nucleotide sequences of a certain region to compare the differences between species. On the majority of the animals, including birds, the cytochrome c oxidase I (COI) gene is widely used for this purpose and in most cases, it shows the ideal greater variation in its sequence among species rather than within individuals of the same species, providing elucidative information about species differentiation. Choosing primers for a DNA barcode application is a crucial step because it depends on the aim of the study and on the taxonomic group of interest. Primers in silico analysis can evaluate its physicochemical properties, the number of species reached by them and then direct the choice of the best primers for the different research objectives, saving time and money resources. Therefore, this present work aimed to answer questions related to the efficiency of the available primers for the avian COI gene and to the avian mitochondrial genome sequences available in databases: i) What is the taxonomic coverage (number of species) reached by the avian COI gene primers? Are the universal primers actually capable of covering all species?; ii) Which avian orders have the most mitochondrial genome sequences available on the databases and what is its representativeness significance within the total number of species for each order?; iii) Which primers show the ideal physicochemical properties to increase the chances of successful amplification in laboratorial experiments? and; iv) Which primer sets are the most suited to guarantee full species recovery within the avian group?